Numerical prediction of concrete slab response to blast loading - Zhou, X.; Kuznetsov, V.; Hao, Hong; Waschl, J. (Pergamon, 2008)
In this paper, a dynamic plastic damage model for concrete material has been employed to estimate responses of both an ordinary reinforced concrete slab and a high strength steel fibre concrete slab subjected to blast loading. In the concrete material model, the strength envelope is a damage-based modified piece-wise Drucker-Prager model; the strain rate effect on tension and compression are considered separately; the damage variable is based on Mazars' damage model, which is a combination of tensile and compressive damage. The equation of state (EOS) is also a combination of the porous and solid EOS of concrete with different forms for tension and compression states. The interaction between the blast wave and the concrete slab is considered in the 3D simulation. In the first stage, the initial detonation and blast wave propagation is modelled in a 2D simulation before the blast wave reaches the concrete slab, then the results obtained from the 2D calculation are remapped to a 3D model. The calculated blast load is compared with that obtained from TM5-1300. The numerical results of the concrete slab response are compared with the explosive tests carried out in the Weapons System Division, Defence Science and Technology Organisation, Department of Defence, Australia. Repetitive applications of blast loading on slabs are also simulated and the results compared with test data.